Linking past uses of legacy SVOCs with today's indoor levels and human exposure - Demirtepe, Hale; Melymuk, Lisa; Diamond, Miriam L; Bajard, Lola; Vojta, Šimon; Prokeš, Roman; Sáňka, Ondřej; Klánová, Jana; Palkovičová Murínová, Ľubica; Richterová, Denisa; Rašplová, Vladimíra; Trnovec, Tomáš (Environment international, 2019)
Semivolatile organic compounds (SVOCs) emitted from consumer products, building materials, and indoor and outdoor activities can be highly persistent in indoor environments. Human exposure to and environmental contamination with polychlorinated biphenyls (PCBs) was previously reported in a region near a former PCB production facility in Slovakia. However, we found that the indoor residential PCB levels did not correlate with the distance from the facility. Rather, indoor levels in this region and those reported in the literature were related to the historic PCB use on a national scale and the inferred presence of primary sources of PCBs in the homes. Other SVOCs had levels linked with either the activities in the home, e.g., polycyclic aromatic hydrocarbons (PAHs) with wood heating; or outdoor activities, e.g., organochlorine pesticides (OCPs) with agricultural land use and building age. We propose a classification framework to prioritize SVOCs for monitoring in indoor environments and to evaluate risks from indoor SVOC exposures. Application of this framework to 88 measured SVOCs identified several PCB congeners (CB-11, -28, -52), hexachlorobenzene (HCB), benzo(a)pyrene, and γ-HCH as priority compounds based on high exposure and toxicity assessed by means of toxicity reference values (TRVs). Application of the framework to many emerging compounds such as novel flame retardants was not possible because of either no or outdated TRVs. Concurrent identification of seven SVOC groups in indoor environments provided information on their comparative levels and distributions, their sources, and informed our assessment of associated risks.
Keywords: Organic Chemicals; Environmental Monitoring; Pesticides; Flame retardants; polychlorované bifenyly; monitorování životního prostředí; Risk prioritization; pesticidy; Humans; Human intake; Legacy POPs; PAHs; lidé; Indoor environment; organické látky; znečištění vzduchu ve vnitřním prostředí; Air Pollution, Indoor; Polychlorinated Biphenyls